Preparation method and application of supported FeRu alloy electrocatalyst
Through the preparation method of the supported FeRu alloy electrocatalyst, the existing problem of low hydrogen production efficiency of alkaline electrolytic water is solved, and the efficient and low-cost alkaline electrolytic aquatic hydrogen production effect is achieved.
Patent Information
- Application Number
- CN202411099987.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-12
- Publication Date
- 2025-02-18
AI Technical Summary
The existing alkaline electrolytic water hydrogen production efficiency is low, and the existing electrocatalyst is costly, which limits its wide application.
By using the method of preparing a supported FeRu alloy electrocatalyst, a supported FeRu alloy electrocatalyst with a particle size of 1 to 5 nm was prepared by heat treatment of the soluble precursor Fe2+ salt and Ru3+ salt in a reducing atmosphere.
The efficiency of electrolyzing freshwater and seawater hydrogen in alkaline environments is improved, the cost of use of precious metals is reduced, and the catalyst has excellent quality activity and high material utilization.
Smart Images

Figure CN119465251A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of hydrogen production by electrolysis of water, and in particular to a preparation method and application of a supported FeRu alloy electrocatalyst. Background Art
[0002] Hydrogen (H2) has the characteristics of high energy density and pollution-free combustion, so it is generally considered to be a renewable clean energy that can solve the energy crisis and environmental pollution. Hydrogen production by electrolysis of fresh water is currently the most effective hydrogen production technology, with a simple operation process, high hydrogen purity, and can use renewable energy to achieve "zero carbon" production. In addition, the global seawater resources are abundant, and H2 can be produced on a large scale by electrocatalysis, which is an efficient and environmentally friendly strategy. In the process of hydrogen production by electrolysis, acidic hydrogen evolution lacks cheap and efficient electrode materials for simultaneous oxygen evolution reaction. Therefore, hydrogen evolution by electrolysis of water in alkaline medium is the most likely technology to form industrial hydrogen production. However, electrolysis of water requires a high overpotential, which will cause a lot of energy consumption, so efficient and stable electrocatalysts are needed to reduce the required overpotential. It can be seen that finding efficient and cheap electrocatalysts for alkaline water electrolysis hydrogen evolution reaction (HER) has important research value and application value.
[0003] At present, platinum (Pt) and Pt-based electrocatalysts are considered to be the best HER electrocatalysts, but their low reserves and high costs limit their widespread application. Transition metals are relatively cheap and have certain electrocatalytic activity, but the activity and stability of these materials are far behind those of precious metal Pt-based catalysts, far from meeting the needs of industrial applications. Ruthenium (Ru) is only one-fifth the cost of Pt, has suitable hydrogen bonding energy and a lower water decomposition barrier, and is expected to become a promising electrocatalyst to replace Pt. Therefore, introducing transition metals into precious metals, such as forming alloy electrocatalysts, has been used as an effective strategy to adjust the degree of water adsorption and dissociation to optimize the electronic structure of electrocatalysts and improve catalytic performance.
[0004] Therefore, the present invention is proposed to improve the method for preparing nano alloy catalysts and to increase the efficiency of hydrogen production by alkaline water electrolysis. Summary of the invention
[0005] 1. Technical issues to be resolved
[0006] In view of the shortcomings of the prior art, the present invention provides a method for preparing a supported FeRu alloy electrocatalyst and its application, which solves the technical problem of low efficiency of hydrogen production by alkaline water electrolysis.
[0007] (II) Technical solution
[0008] To achieve the above objectives, the present invention is implemented through the following technical solutions:
[0009] The preparation method of the supported FeRu alloy electrocatalyst specifically comprises the following steps:
[0010] S1, firstly, the soluble precursor Fe 2+ Salt, Ru 3+ The salt and the carrier are ultrasonically dispersed in the solvent, and the precursor is synthesized by condensation reflux in an oil bath;
[0011] S2. The prepared precursor is heat-treated in a reducing atmosphere, and then filtered, washed and dried to obtain a supported FeRu alloy electrocatalyst with a particle size of 1 to 5 nm.
[0012] Preferably, the specific steps of S1 are: weighing Fe 2+ Salt, Ru 3+ Salt is dissolved in a mixed solution of ethylene glycol / polyethylene glycol and water, a carrier is added to the mixed solution, the mixture is evenly dispersed by ultrasonication for 30 min to 120 min, transferred to an oil bath and reacted at 120° C. to 250° C. for 4 h to 8 h, naturally cooled to room temperature, then filtered and washed with ethanol, and dried at 60° C. for 12 h to obtain a precursor.
[0013] Preferably, the specific method of oil bath heating in S1 is: heating from room temperature to 120°C to 250°C at 1 to 5°C / min under oil bath conditions, reacting for 4 to 8 hours, and then naturally cooling to room temperature.
[0014] Preferably, the specific steps of S2 are: heating the precursor from room temperature to 250°C to 550°C at a rate of 5 to 10°C / min in a tube furnace, maintaining it for 1h to 3h in a 5% H2 / Ar atmosphere, then cooling it to room temperature, washing the supported FeRu alloy electrocatalyst sample with water and ethanol, and heating it to 60°C and drying it for 12h to obtain a supported FeRu alloy electrocatalyst.
[0015] Preferably, the Fe 2+ The salt accounts for 5wt% to 15wt% of the carrier, and the Ru 3+ The salt accounts for 5 wt% to 10 wt% of the carrier.
[0016] Preferably, the Fe 2+ The salt is selected from any one of FeCl2·4H2O, FeCl2, FeSO4, Fe(NO3)2, wherein the Ru 3+ The salt is selected from any one of RuCl3 and RuCl3·3H2O.
[0017] Preferably, the Fe 2+ The salt solution and the Ru 3+ The molar ratio of Fe element to Ru element in the salt solution is (1-3):1.
[0018] Preferably, the carrier is selected from any one of XC-72, carbon nanotubes and Ketjen black.
[0019] Preferably, the vector is XC-72.
[0020] The FeRu alloy electrocatalyst prepared by the preparation method of the loaded FeRu alloy electrocatalyst as mentioned above is applied to the technical field of hydrogen production by alkaline electrolysis of fresh water and seawater, specifically for modification on the surface of glassy carbon electrode, and electrocatalytic hydrogen production test is carried out in alkaline fresh water and seawater environment, and the solution is 1M KOH, 1M KOH+0.5M NaCl and 1M KOH+seawater.
[0021] (III) Beneficial effects
[0022] The present invention provides a preparation method and application of a supported FeRu alloy electrocatalyst. Compared with the prior art, it has the following beneficial effects:
[0023] 1. The preparation method of the supported FeRu alloy electrocatalyst prepared by the present invention has a simple preparation process, mild conditions, low precious metal content and low cost compared with the prior art, and provides a new idea for the preparation method of synthetic nano alloy electrocatalysts;
[0024] 2. The supported FeRu alloy electrocatalyst prepared by the present invention is a spherical metal particle with a diameter of 1 to 5 nm. Compared with bulk metal particles, it has more active surface area and catalytic active sites to improve catalytic activity and material utilization efficiency, and has excellent mass activity, which greatly improves material utilization and reduces the cost of precious metals.
[0025] 3. The FeRu alloy electrocatalyst prepared by the present invention can induce an electronic effect and generate a stronger H + The adsorption capacity can be further improved, and the efficiency of hydrogen production by electrolysis of fresh water and seawater in alkaline environment can be further improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0027] Figure 1 It is a schematic diagram of the preparation of the supported FeRu alloy electrocatalyst of the present invention;
[0028] Figure 2The supported Fe prepared in Example 1 of the present invention 0.05 Ru 0.05 -X-ray diffraction pattern (XRD) of alloy electrocatalyst at 350℃;
[0029] Figure 3 The supported Fe prepared in Example 1 of the present invention 0.05 Ru 0.05 -High resolution transmission electron microscopy (HRTEM) and particle size distribution of the alloy electrocatalyst at 350°C (ab);
[0030] Figure 4 The supported Fe prepared in Example 1 of the present invention 0.05 Ru 0.05 -350℃ alloy electrocatalyst, commercial Pt / C and Ru prepared in Comparative Example 1 0.05 Linear sweep voltammetric performance graph and performance comparison bar graph (d) of electrocatalytic hydrogen production of / XC-72-350℃ in 1M KOH (a), 1M KOH+0.5MNaCl (b) and 1M KOH+SeaWater (c) solutions, with the reversible hydrogen electrode as the reference electrode;
[0031] Figure 5 The supported Fe prepared in Example 1 of the present invention 0.05 Ru 0.05 -350℃ alloy electrocatalyst in 1M KOH solution for electrocatalytic hydrogen production reaction. Normalized polarization curves of noble metals (a) and mass activity comparison bar graphs (b), with reversible hydrogen electrode as reference electrode.
[0032] Figure 6 The supported Fe prepared in Example 1 of the present invention 0.05 Ru 0.05 -350℃ alloy electrocatalyst current-time curve in 1M KOH solution and polarization curves after the 1st and 1000th cycles;
[0033] Figure 7 The supported Fe prepared in Example 1 of the present invention 0.05 Ru 0.05 -XRD pattern (a), transmission electron microscopy (TEM) pattern (b) and HRTEM pattern (c) of the alloy electrocatalyst at -350℃ after catalyst stability test in 1M KOH solution;
[0034] Figure 8 It is a linear sweep voltammetric curve performance diagram of the alloy catalysts prepared in Example 1 and Examples 5-7 of the present invention for electrocatalytic hydrogen production in 1M KOH solution. DETAILED DESCRIPTION
[0035] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention are clearly and completely described. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0036] The embodiments of the present application solve the technical problem of low efficiency of hydrogen production by alkaline water electrolysis by providing a preparation method and application of a supported FeRu alloy electrocatalyst.
[0037] In order to better understand the above technical solution, the above technical solution will be described in detail below in conjunction with the accompanying drawings and specific implementation methods.
[0038] The carrier of the present invention can be selected from any one of XC-72, carbon nanotubes, and Ketjen black. The carriers selected in the following embodiments are all XC-72.
[0039] Example 1
[0040] like Figure 1 As shown, the preparation method of the supported FeRu alloy electrocatalyst comprises the following steps:
[0041] S1. Ultrasonic dispersion of 0.02 mmol FeCl2·4H2O and 0.02 mmol RuCl3 in a mixed solution of 120 mL ethylene glycol and water, adding 200 mg XC-72 to the mixture, ultrasonication time for 60 min, transferring to an oil bath, heating from room temperature to 130°C at 2°C / min, reacting for 6 h, naturally cooling to room temperature, then filtering and washing with ethanol, and drying at 60°C for 12 h to obtain a precursor;
[0042] S2. The precursor was heated from room temperature to 350°C at a rate of 5°C / min in a tube furnace and maintained for 3 h in a 5% H2 / Ar atmosphere, then cooled to room temperature, the supported FeRu alloy electrocatalyst sample was washed with water and ethanol, and the temperature was raised to 60°C and dried for 12 h to obtain FeRu. 0.05 Ru 0.05 / XC-72-350℃ alloy electrocatalyst.
[0043] Figure 2 The supported Fe prepared in Example 1 0.05 Ru 0.05 / XC-72-350℃ and Ru prepared in Comparative Example 1 0.05 The XRD pattern of the / XC-72-350℃ electrocatalyst shows that its characteristic diffraction peak corresponds to the standard diffraction peak of Ru and has a similar crystal structure.0.05 / XC-72-350℃(JCPDS NO.:06-0663), Fe 0.05 Ru 0.05 The diffraction peaks of the / XC-72-350℃ sample shift slightly to lower diffraction angles, indicating a strong correlation between Fe and Ru, which proves the successful synthesis of supported FeRu alloy.
[0044] Figure 3 The Fe prepared in Example 1 0.05 Ru 0.05 HRTEM image and particle size distribution of / XC-72-350℃ alloy electrocatalyst. Figure 3 As shown in (ab), Fe 0.05 Ru 0.05 / XC-72-350℃ The average particle size of the electrocatalyst metal particles is 2.1nm and they are evenly dispersed on the carbon carrier. The carbon carrier plays an important role in preventing particle aggregation, achieving ultra-small nanoparticles and improving dispersion uniformity.
[0045] Figure 4 The Fe prepared in Example 1 0.05 Ru 0.05 / XC-72-350℃ alloy electrocatalyst and commercial Pt / C, Ru prepared in Comparative Example 1 0.05 / XC-72-350℃ sample catalyst was used as cathode material, and the current-time curve and performance comparison bar graph of electrocatalytic hydrogen production reaction were carried out in 1M KOH, 1MKOH+0.5M NaCl and 1MKOH+Sea Water solutions respectively. Figure 4 (ad) It can be seen that compared with commercial Pt / C and Ru 0.05 / XC-72-350℃ electrocatalyst, Fe prepared in Example 1 0.05 Ru 0.05 The / XC-72-350℃ alloy electrocatalyst has the lowest hydrogen production overpotential of 13mV, 15mV and 18mV in 1M KOH, 1M KOH+0.5M NaCl and 1M KOH+Sea Water solutions, which proves that the material of the present invention has excellent performance in hydrogen production in alkaline water electrolysis.
[0046] Figure 5 The supported Fe prepared in Example 1 0.05 Ru 0.05 / XC-72-350℃ alloy electrocatalyst and commercial Pt / C catalyst were used as cathode materials. Normalized polarization curves and mass activity comparison bar graphs of precious metals during electrocatalytic hydrogen production reaction in 1M KOH solution, with the reversible hydrogen electrode as the reference electrode. Figure 5(ab) shows that at a voltage of -0.07 V, Fe 0.05 Ru 0.05 / XC-72-350℃ electrocatalyst showed good mass activity (11.32A mg noble metal-1 -0.07Vvs.RHE), which was better than 20% Pt / C (0.16A mg noble metal-1) and Ru 0.05 / XC-72-350℃(0.33A mgnoble metal-1), the mass activity in 1M KOH solution is the same as that of commercial Pt / C and comparative sample Ru 0.05 / XC-72-350℃ catalyst is 71 times and 34 times, which can prove that the material of the present invention has a higher precious metal utilization rate and excellent performance when used as a catalyst for hydrogen production by electrolysis of water.
[0047] Figure 6 The Fe prepared in Example 1 0.05 Ru 0.05 / XC-72-350℃ alloy electrocatalyst is used as cathode material. The current-time curve of electrocatalytic hydrogen production reaction in 1MKOH solution shows that the current density of the material of the present invention is basically maintained at 100% after 24 hours, and has good catalytic stability. Similar results were obtained for continuous cyclic voltammetry. The cyclic voltammetry test was performed for 1000 cycles to evaluate the durability of the catalytic material. After the cycle, Fe 0.05 Ru 0.05 The LSV curve of the / XC-72-350 °C electrocatalyst almost overlaps with the initial scan, which can be attributed to the almost unchanged phase composition and morphology.
[0048] Figure 7 The XRD (a) and HRTEM (bc) results show that after the electrochemical stability test, Fe 0.05 Ru 0.05 / XC-72-350℃, its morphology and structure are basically unchanged. The above results fully prove that the supported Fe prepared by the present invention 0.05 Ru 0.05 -350℃ alloy electrocatalyst has good catalytic performance and stability when used in alkaline water electrolysis.
[0049] Embodiment 2:
[0050] The preparation method of the supported FeRu alloy electrocatalyst comprises the following steps:
[0051] S1. Ultrasonic dispersion of 0.02 mmol FeCl2·4H2O and 0.02 mmol RuCl3 in a mixed solution of 120 mL ethylene glycol and water, adding 200 mg XC-72 to the mixture, ultrasonication time for 120 min, transferring to an oil bath, heating from room temperature to 120°C at 1°C / min, reacting for 8 h, naturally cooling to room temperature, then filtering and washing with ethanol, and drying at 60°C for 12 h to obtain a precursor;
[0052] S2. The precursor was heated from room temperature to 350°C at a rate of 10°C / min in a tube furnace and maintained for 3 h in a 5% H2 / Ar atmosphere, then cooled to room temperature, the supported FeRu alloy electrocatalyst sample was washed with water and ethanol, and the temperature was raised to 60°C and dried for 12 h to obtain FeRu. 005 Ru 005 -350℃ alloy electrocatalyst.
[0053] Embodiment 3:
[0054] The preparation method of the supported FeRu alloy electrocatalyst comprises the following steps:
[0055] S1. Ultrasonic dispersion of 0.04mmol FeCl2·4H2O and 0.02mmol RuCl3 in a mixed solution of 120mL ethylene glycol and water, adding 200mg XC-72 to the mixture, ultrasonication time for 120min, transferring to an oil bath, heating from room temperature to 250℃ at 5℃ / min, reacting for 4h, cooling naturally, filtering, washing and drying to obtain a precursor;
[0056] S2. The precursor was heated from room temperature to 350°C at a rate of 5°C / min in a tube furnace and maintained for 3 h in a 5% H2 / Ar atmosphere, then cooled to room temperature, the supported FeRu alloy electrocatalyst sample was washed with water and ethanol, and the temperature was raised to 60°C and dried for 12 h to obtain FeRu. 0.1 Ru 0.05 -350℃ alloy electrocatalyst.
[0057] Example 4
[0058] The preparation method of the supported FeRu alloy electrocatalyst comprises the following steps:
[0059] S1. Ultrasonic dispersion of 0.04mmol FeCl2·4H2O and 0.02mmol RuCl3 in a mixed solution of 120mL ethylene glycol and water, adding 200mg XC-72 to the mixture, ultrasonication time for 120min, transferring to an oil bath, heating from room temperature to 250℃ at 5℃ / min, reacting for 4h, cooling naturally, filtering, washing and drying to obtain a precursor;
[0060] S2. The precursor was heated from room temperature to 550°C at 5°C / min in a tube furnace and maintained for 3 h in a 5% H2 / Ar atmosphere, then cooled to room temperature, the supported FeRu alloy electrocatalyst sample was washed with water and ethanol, and the temperature was raised to 60°C and dried for 12 h to obtain FeRu. 0.1 Ru 0.05 -350℃ alloy electrocatalyst.
[0061] Embodiment 5 is different from Embodiment 1 in that:
[0062] The precursor was heated from room temperature to 250°C at 5°C / min in a tube furnace.
[0063] Prepare Fe 0.05 Ru 0.05 / XC-72-250℃ alloy electrocatalyst.
[0064] Embodiment 6 is different from Embodiment 1 in that:
[0065] The precursor was heated from room temperature to 450°C in a tube furnace at a rate of 5°C / min.
[0066] Prepare Fe 0.05 Ru 0.05 / XC-72-450℃ alloy electrocatalyst.
[0067] Embodiment 7 is different from Embodiment 1 in that:
[0068] The precursor was heated from room temperature to 550°C at 5°C / min in a tube furnace.
[0069] Prepare Fe 0.05 Ru 0.05 / XC-72-550℃ alloy electrocatalyst.
[0070] The Fe prepared in Example 1 0.05 Ru 0.05 The performance of the / XC-72-350℃ alloy electrocatalyst was compared with the catalyst prepared in Examples 5-7. The results are shown in Figure 8 , Fe 0.05 Ru 0.05 / XC-72-350℃ at 10mA cm -2 The lowest overpotential was 13 mV, which was better than that of Fe prepared in Example 5. 0.05 Ru 0.05 / XC-72-250℃(at 10mA cm -2 38mV), Fe prepared in Example 6 0.05 Ru 0.05 / XC-72-450℃(at 10mA cm -2 16mV) and Fe prepared in Example 7 0.05 Ru 0.05 / XC-72-550℃(10mA cm -2 23mV when
[0071] Example 8
[0072] The supported FeRu alloy electrocatalyst prepared in any one of Examples 1-3 is applied to the technical field of hydrogen production by alkaline electrolysis of fresh water and seawater, specifically used to modify the surface of a glassy carbon electrode, and electrocatalytic hydrogen production tests are carried out in alkaline fresh water and seawater environments, with the solutions being 1M KOH, 1M KOH+0.5M NaCl and 1M KOH+seawater.
[0073] Comparative Example 1
[0074] Ru 0.05 / Synthesis of XC-72:
[0075] Weigh 200 mg XC-72 and 0.02 mmol RuCl3 and prepare Ru by the method of Example 1. 0.05 / XC-72-350℃ electrocatalyst.
[0076] Comparative Example 2
[0077] Weigh 200 mg XC-72, 0.1 mmol FeCl2·4H2O and 0.02 mmol RuCl3, and prepare Fe 0.1 Ru 0.05 / XC-72-350℃ electrocatalyst.
[0078] Experimental tests show that the electrocatalyst has the lowest hydrogen production overpotential of 25mV, 27mV and 30mV in 1M KOH, 1M KOH+0.5M NaCl and 1MKOH+Sea Water solutions.
[0079] Comparative Example 3
[0080] Weigh 200 mg XC-72, 0.02 mmol FeCl2·4H2O and 0.1 mmol RuCl3, and prepare Fe 0.05 Ru 0.1 / XC-72-350℃ electrocatalyst.
[0081] Experimental tests show that the electrocatalyst has the lowest hydrogen production overpotential of 20 mV, 23 mV and 26 mV in 1 M KOH, 1 M KOH+0.5 M NaCl and 1 M KOH+Sea Water solutions.
[0082] Comparative Example 4
[0083] Weigh 200 mg XC-72, 0.1 mmol FeCl2·4H2O and 0.1 mmol RuCl3, and prepare Fe 01 Ru 01 / XC-72-350℃ electrocatalyst.
[0084] Experimental tests show that the electrocatalyst has the lowest hydrogen production overpotential of 32 mV, 33 mV and 35 mV in 1 M KOH, 1 M KOH+0.5 M NaCl and 1 M KOH+Sea Water solutions.
[0085] In summary, compared with the prior art, the present invention has the following beneficial effects:
[0086] 1. The preparation method of the supported FeRu alloy electrocatalyst prepared by the present invention has a simple preparation process, mild conditions, low precious metal content and low cost compared with the prior art, and provides a new idea for the preparation method of synthetic nano alloy electrocatalysts;
[0087] 2. The supported FeRu alloy electrocatalyst prepared by the present invention is a spherical metal particle with a diameter of 1 to 5 nm. Compared with bulk metal particles, it has more active surface area and catalytic active sites to improve catalytic activity and material utilization efficiency, and has excellent mass activity, which greatly improves material utilization and reduces the cost of precious metals.
[0088] 3. The FeRu alloy electrocatalyst prepared by the present invention can induce an electronic effect and generate a stronger H + The adsorption capacity can be further improved, and the efficiency of hydrogen production by electrolysis of fresh water and seawater in alkaline environment can be further improved.
[0089] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, the elements defined by the sentence "comprise a ..." do not exclude the existence of other identical elements in the process, method, article or device including the elements.
[0090] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing a supported FeRu alloy electrocatalyst, characterized in that: The specific steps include: S1, firstly, the soluble precursor Fe 2+ Salt, Ru 3+ The salt and the carrier are ultrasonically dispersed in the solvent, and the precursor is synthesized by condensation reflux in an oil bath; S2. The prepared precursor is subjected to heat treatment in a reducing atmosphere, and then filtered, washed and dried to obtain a supported FeRu alloy electrocatalyst with a particle size of 1 to 5 nm.
2. The method for preparing a supported FeRu alloy electrocatalyst according to claim 1, characterized in that: The specific steps of S1 are: weighing Fe 2+ Salt, Ru 3+ Salt is dissolved in a mixed solution of ethylene glycol / polyethylene glycol and water, a carrier is added to the mixed solution, the mixture is evenly dispersed by ultrasonication for 30 min to 120 min, transferred to an oil bath and reacted at 120° C. to 250° C. for 4 h to 8 h, naturally cooled to room temperature, then filtered and washed with ethanol, and dried at 60° C. for 12 h to obtain a precursor.
3. The method for preparing a supported FeRu alloy electrocatalyst according to claim 2, characterized in that: The specific method of the oil bath heating in S1 is: heating from room temperature to 120°C to 250°C at a rate of 1 to 5°C / min under oil bath conditions, reacting for 4 to 8 hours, and then naturally cooling to room temperature.
4. The method for preparing a supported FeRu alloy electrocatalyst according to claim 1, characterized in that: The specific steps of S2 are: heating the precursor from room temperature to 250°C to 550°C at a rate of 5 to 10°C / min in a tubular furnace, maintaining it for 1 to 3 hours in a 5% H2 / Ar atmosphere, and then cooling it to room temperature, washing the crude product of the supported FeRu alloy electrocatalyst with water and ethanol, and heating it to 60°C and drying it for 12 hours to obtain a supported FeRu alloy electrocatalyst.
5. The method for preparing a supported FeRu alloy electrocatalyst according to claim 1, characterized in that: The Fe 2+ The salt accounts for 5wt% to 15wt% of the carrier, and the Ru 3+ The salt accounts for 5 wt% to 10 wt% of the carrier.
6. The method for preparing a supported FeRu alloy electrocatalyst according to claim 1, characterized in that: The Fe 2+ The salt is selected from any one of FeCl2·4H2O, FeCl2, FeSO4, Fe(NO3)2, wherein the Ru 3+ The salt is selected from any one of RuCl3 and RuCl3·3H2O.
7. The method for preparing a supported FeRu alloy electrocatalyst according to claim 1, characterized in that: The Fe 2+ The salt solution and the Ru 3+ The molar ratio of Fe element to Ru element in the salt solution is (1-3):
1.
8. The method for preparing a supported FeRu alloy electrocatalyst according to claim 1, characterized in that: The carrier is selected from any one of XC-72, carbon nanotubes and Ketjen black.
9. The method for preparing a supported FeRu alloy electrocatalyst according to claim 8, characterized in that: The vector is XC-72.
10. The FeRu alloy electrocatalyst prepared by the preparation method of the supported FeRu alloy electrocatalyst according to any one of claims 1 to 9 is applied to the technical field of hydrogen production by alkaline electrolysis of fresh water and seawater, specifically for modification on the surface of a glassy carbon electrode, and electrocatalytic hydrogen production tests are carried out in alkaline fresh water and seawater environments, and the solutions are 1M KOH, 1M KOH+0.5M NaCl and 1M KOH+seawater.